Formation of Efficient Dye-Sensitized Solar Cells by Introducing an Interfacial Layer of Long-Range Ordered Mesoporous TiO2 Thin Film - Kim, Yong Joo; Lee, Yoon Hee; Lee, Mi Hyeon; Kim, Hark Jin; Pan, Jia Hong; Lim, Goo Il; Choi, Young S.; Kim, Kyungkon; Park, Nam-Gyu; Lee, Chongmu; Lee, Wan In (AMER CHEMICAL SOC, 2008)
Long-range ordered cubic mesoporous TiO2 films with 300 nm thickness were fabricated on fluorine-doped tin oxide (FTO) substrate by evaporation-induced self-assembly (EISA) process using F127 as a structure-directing agent. The prepared mesoporous TiO2 film (Meso-TiO2) was applied as an interfacial layer between the nanocrystalline TiO2 film (NC-TiO2) and the FTO electrode in the dye-sensitized solar cell (DSSC). The introduction of Meso-TiO2 increased J(sc) from 12.3 to 14.5 mA/cm(2), and V-oc by 55 mV, whereas there was no appreciable change in the fill factor (FF). As a result, the photovoltaic conversion efficiency (eta) was improved by 30.0% from 5.77% to 7.48%. Notably, introduction of Meso-TiO2 increased the transmittance of visible light through the FTO glass by 23% as a result of its excellent antireflective role. Thus the increased transmittance was a key factor in enhancing the photovoltaic conversion efficiency. In addition, the presence of interfacial Meso-TiO2 provided excellent adhesion between the FTO and main TiO2 layer, and suppressed the back-transport reaction by blocking direct contact between the electrolyte and FTO electrode.
Keywords: TITANIUM-DIOXIDE; ELECTRON-TRANSPORT; METAL-OXIDES; LOW-COST; RECOMBINATION; PERFORMANCE; CONVERSION; COPOLYMER; DIFFUSION; TRIBLOCK